1996
DOI: 10.1037/1076-8998.1.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Current issues relating to psychosocial job strain and cardiovascular disease research.

Abstract: The authors comment on recent reviews of cardiovascular job strain research by P. L. Schnall and P. A. Landsbergis (1994), and by T. S. Kristensen (1995), which conclude that job strain as defined by the demand-control model (the combination of contributions of low job decision latitudes and high psychological job demands) is confirmed as a risk factor for cardiovascular mortality in a large majority of studies. Lack of social support at work appears to further increase risk. Several still-unresolved research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
552
4
55

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 727 publications
(637 citation statements)
references
References 75 publications
26
552
4
55
Order By: Relevance
“…These problems are exemplified by evidence related to the stress-buffering effect of control, as postulated by the job-demands-control model (65). This stressbuffering effect is found only for people who have the internal (or personal) resources to use control (a structural resource) effectively.…”
Section: Methodological Aspectsmentioning
confidence: 97%
“…These problems are exemplified by evidence related to the stress-buffering effect of control, as postulated by the job-demands-control model (65). This stressbuffering effect is found only for people who have the internal (or personal) resources to use control (a structural resource) effectively.…”
Section: Methodological Aspectsmentioning
confidence: 97%
“…In the past, various self-report measures of job strain have been linked with cardiovascular mortality (Theorell & Karasak, 1996). The composite measures, pulse pressure and pulse product, provide firsthand, objective measurements of cardiovascular health and efficiency.…”
Section: The Over-reliance On Self-report Datamentioning
confidence: 99%
“…12,13 Workers in high-strain jobs have an increased risk for the development of cardiovascular diseases. 20 Later, another dimension, social support, was added to the theory. 13 Studies regarding job demands, job control, and musculoskeletal symptoms 9 reported associations not only between musculoskeletal symptoms and psychological job demands, but also found that psychological job demands were related to high levels of physical exertion on the job.…”
Section: Introductionmentioning
confidence: 99%